Phytotherapy in the control of helminthiasis in production animals - Peixoto, Erika Cosendey Toledo de Mello; Andrade, Andressa de; Valadares, Fillipi; Silva, Luciana Pereira [UNESP]; Silva, Regildo Márcio Gonçalves da [UNESP] (My University, 2013)
Parasitic diseases constitute one of the main problems affecting livestock; however the use of chemical medicaments provides drug resistance residues in animal and environmental contamination. Changes in production concepts require that food must be produced in hygienic conditions, per healthy animals and that are not eliminating antibiotic residues, pesticides or other drugs. This scenario has favored organic production and the use of medicinal plants. For the control of endoparasites, several studies have published the benefits of Azadirachta indica A. Juss., Punica granatum Linn., Musa sp., Operculina hamiltonii G. DON., propolis, among others. However, despite the existence in- vitro studies that demonstrate the pharmacological properties of phytotherapics, there is still need for clinical trials to determine dosage and its effects in- vivo. Investigations of new bioactive natural substances can be of great value for the control of animal health and food safety, which is particularly important for organic production systems in which the use of chemical drugs is a limiting factor for certification.
Keywords: Agroecology; biological agriculture; medicinal plants; parasitic worms